2019
DOI: 10.1016/j.chemosphere.2019.02.173
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic assessment of Microcystin-LR, cylindrospermopsin and their combination on the human neuroblastoma SH-SY5Y cell line

Abstract: Microcystin-LR (MC-LR) and Cylindrospermopsin (CYN) are produced by cyanobacteria. Although being considered as a hepatotoxin and a cytotoxin, respectively, different studies have revealed neurotoxic properties for both of them. The aim of the present work was to study their cytotoxic effects, alone and in combination, in the SH-SY5Y cell line. In addition, toxicity mechanisms such as oxidative stress and acetylcholinesterase (AChE) activity, and morphological studies were carried out. Results showed a cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 92 publications
(116 reference statements)
4
17
1
Order By: Relevance
“…CYNs primarily target the liver, but it is also a cytotoxin. Recent studies have found that CYNs also cause nervous system damage, and they are more toxic than MCs in terms of neurotoxicity [58,60].…”
Section: Structural Characterizationmentioning
confidence: 99%
“…CYNs primarily target the liver, but it is also a cytotoxin. Recent studies have found that CYNs also cause nervous system damage, and they are more toxic than MCs in terms of neurotoxicity [58,60].…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Even though occurrence data show that MC-RR and other minority MCs are distributed worldwide becoming sometimes predominant, the congener MC-LR is widely distributed and the main focus of toxicological studies [8,64]. The ratio CYN/MC concentrations could oscillate between countries and continents, climatic conditions, or composition of the cyanobacteria communities [44,45], and in this study the ratio 1:10 CYN/MC-LR was chosen to compare or confirm previous toxicity studies in which combinations of CYN/MC-LR were assayed [49][50][51]. Furthermore, the International Conference on Harmonisation (ICH) S2 guidelines [90] and the OECD 474 [53] and OECD 489 [54] guidelines for the MN and Comet assay, respectively, recommend for the combined MN-comet assay the use of the highest dose and two additional lower doses [58] appropriately separated by less than √ 10 to prove dose-related responses [54].…”
Section: Experimental Design and Treatmentmentioning
confidence: 99%
“…A few studies dealt with the toxicological profile of CYN and MC-LR combinations. Thus, the in vitro assessments of the potential interactions of CYN and MC-LR are very scarce [48][49][50][51], and only two focus on their genotoxicity. Hercog et al [48] described an induction of DNA sb by MN and comet assays at 24 h after the treatment of HepG2 cells with CYN/MC-LR combinations, but to a lesser extent for only CYN.…”
Section: Introductionmentioning
confidence: 99%
“…It has detected more than 100 MCs variants, of which microcystin-LR (MC-LR) is the most widely studied (Zhou et al, 2014). Accumulating evidence has shown that MC-LR has various toxic effects containing hepatotoxicity and neurotoxicity (Hinojosa et al, 2019;Wang et al, 2019). In decades, laboratory experiments suggest that male gonad is a considerable target of MC-LR.…”
Section: Introductionmentioning
confidence: 99%